(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
Realistic Mathematical Education (RME) is a method of linking abstract mathematics learning with real life so that mathematics is easy to understand. Suggest that in explaining the calculation work as much as possible so that it begins by using real objects, drawings or diagrams that have something to do with real everyday life. This study aims to determine the implementation of the RME approach in elementary schools based on a literature review conducted. This research uses a qualitative approach with a type of literature study. The data collection technique used is through the study of documentation sourced from relevant books, articles, and references. Data analysis techniques consist of data reduction, data presentation, and conclusions. The results of data analysis show that mathematics teachers need to apply RME in the classroom so that abstract mathematical concepts are easier to understand. RME also helps teachers to simplify and realize mathematical concepts. Therefore, teachers need to be more creative and innovative in designing learning with this approach. Teachers need to develop more appropriate media, strategies, or learning models, according to the learning material or with the context faced by their students